ERICA: use of screens and consumption of meals and snacks by Brazilian adolescents - Juliana Souza Oliveira; Laura Augusta Barufaldi; Gabriela de Azevedo Abreu; Vanessa Sá Leal; Gisela Soares Brunken; Sandra Mary Lima Vasconcelos; Marize Melo dos Santos; Katia Vergetti Bloch (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To describe the length of exposure to screens and the prevalence of consumption of meals and snacks by Brazilian adolescents in front of screens. METHODS We evaluated 74,589 12 to 17-year old adolescents from 1,247 schools in 124 Brazilian municipalities. A self-administered questionnaire was used. Its segment regarding nutrition contained questions about using TV, computers, and video game systems, having meals while watching TV, and consuming snacks in front of screens. Consumption of meals and snacks in front of screens was analyzed according to the following variables: geographical region, gender, age range, type of school (public or private), and school shift. The prevalences and their respective 95% confidence intervals were estimated under a complex sampling design. RESULTS A great deal of the adolescents (73.5%, 95%CI 72.3-74.7) reported spending two or more hours a day in front of screens. That habit was more frequent among male adolescents, private school students, morning shift students, and students from Brazil's South region. More than half of the adolescents (56.6%, 95%CI 55.4-57.8) reported almost always or always having meals in front of TV, and 39.6% (95%CI 38.8-40.5) of them said they consumed snacks in front of screens exactly as often. Both situations were the most prevalent ones among the girls, who attended public schools and were from Brazil's Midwest region. CONCLUSIONS Length of exposure to screens and consumption of meals and snacks almost always or always in front of screens are high among Brazilian adolescents. It is necessary to develop strategies aiming to reduce the length of screen use, considering the media reality that children and adolescents have been experiencing from earlier and earlier ages. That context must therefore be analyzed in an indissociable way.